Implementasi Pendidikan Karakter di SMA Negeri 7 Prabumulih - Wulandari, Catur; Ardiansyah, Rezza; Lestari, Neta Dian (Journal of Innovation in Teaching and Instructional Media, 2024)
Character education is one of the vital aspects in the development of the education system in Indonesia, especially at the secondary school level. By focusing on the experiences and perceptions of teachers, students, and other related parties, this study explores how character values ​​are integrated into learning activities at school. This study aims to analyze the implementation of character education at SMA Negeri 7 Prabumulih through a phenomenological approach. Character education is becoming increasingly important amidst the moral and social challenges faced by today’s young generation. This study examines the experiences of teachers and students in the process of implementing character education and its impact on students’ attitudes and behavior. The implementation of character education has shown significant results in shaping students’ character. The results of this study are expected to be a reference for further research and educational practices in other schools.